Penambahan Osteopontin dalam Pengencer Semen Beku Sapi Perah Friesian Holstein Meningkatkan Ekspresi B-Cell Cll/Lymphoma-2 Spermatozoa Postthawing (ADDITIONAL OSTEOPONTIN INTO FROZEN FRIESIAN-HOLSTEIN SEMEN DILUTER INCREASES THE EXPRESSION OF B-CELL CLL/L - Samik, Abdul; Oktanella, Yudit; Hernawati, Tatik; Widjaja, Ngakan Made Rai; Dewanti, Intan Purwa (Jurnal Veteriner, 2015)
Post thawed frozen semen viability is one of the most important keys in artificial inseminationdepended on two major cell death mechanism, apoptosis and necrosis. It has been known that good fertilitydiary bull’s seminal plasma contains high concentration of osteopontin (OPN). Osteopontin also known ascell survival protein via inhibition to apoptotic cell death, and B-cell CLL/Lymphoma-2 (Bcl-2)expressionmostly related to the ability of cell survival. The aim of this study was to investigate the influence ofadditional OPN into frozen semen diluter on post thawed sperm Bcl-2 expression. Fresh semen collectedfrom ±4 year Friesian Holstein bull. Treatment group divided into four groups i.e.: control group (P0:without OPN supplementation), (P1: fresh semen with OPN supplementation 5 ?g/5.107 spermatozoa), (P2:fresh semen with OPN supplementation 10 ?g/5.107 spermatozoa), (P3: fresh semen with OPNsupplementation 20 ?g/5.107spermatozoa). Bcl-2 sperm expression was determined usingimunocytochemistry. The result of this study showed that there was no significant difference betweengroup P0 and P1 (p>0,05), but both group P2 and group P3 showed a significant difference with P0 (p<0,05).Nevertheless, there was no significant difference between group P2to group P3 on post thawed FriesianHolstein sperm Bcl-2 expression (p>0,05). The conclusion of this study is osteopontin supplement in frozensemen diluter is capable to increase post thawed Friesian Holstein sperm Bcl-2 expression.
Keywords: osteopontin, Bcl-2 expression, semen diluter, dairy bull’s sperm